CONCEPÇÕES DE PROFESSORES: Sentidos e significados do ensino da arte na escola como espaço de humanização - Lechuga, Evelyn Bendó (2022)
This investigation is associated with the “Formative processes, educational practices, differences” line of research of Universidade Federal de Mato Grosso do Sul (UFMS)’s Postgraduate Program in Education. It has the goal to analyse the senses and meanings of teaching Art in the school environment from the point of view of the Art Teachers. Facing the goal what is problematized: What is: the concept of the teachers regarding the teaching of Art into the school space, which brings senses and meanings for them to recognize the art as a humanizing process? For that pursuit the theoretical input anchors itself in the cultural-historical theory based on the historic-dialectical materialism. For that purpose, we’ve conducted interviews with five Art teachers from the Municipal Educational System of Campo Grande in Mato Grosso do Sul state, in the segment of “Ensino fundamental anos iniciais e finais” (the equivalent of elementary school from first to 9th grade. The interviews were organized in two units of development and analysis, and art at school. The results, still partial, point out that in the teachers’ testimonies, even when facing difficulties, creativity is the most relevant point of the process of art teaching, what moves away from the possibility of comprehension that the transmission of knowledge values the art in relation to the classic contents, contents that the teacher organizes intentionally for the students to own the knowledge accumulated by mankind. Therefore, the meanings and definitions do not unveil the possibility of recognizing that art can enable the humanization in the school space.